The centrality of the Quran in dealing with the phenomenon of divorce - benyamina, Khaldia abdelkader (Journal of Islamic Sciences, 2019)
I have tried through my studies to appreciate the efforts of researchers who dealt with the issue of divorce, summarize the sum of their ideas in it or more remind us of our youth and those concerned with the danger of divorce, which has become a strange phenomenon, and an unusual event razed the body of our Muslim society or nearly, despite the existence of what it organizes and limits In the Holy Quran, which emphasized the moderation and moderation in the management of human affairs and the universe, as the provisions and laws surrounded by the Koran divorce aims to maintain human relations based on housing and affection and mercy, and restrict or narrowing the circle of divorce by specifying the number Shots and staging them, and limit the causes and disobedience B who tamper with it and exceed the limits of God, and follow him by restricting and paid by the provisions of the kit and the expense of mediation mediated by divorce and made them a tool of reconciliation and treatment and review more than the tool of separation and division and destruction, without arbitrariness in the kit prolongation of , And in the expense of the husband’s insolvency to spend above the cost itself, as well as that the Holy Quran was an average when equated between the parties to the marriage in the request for divorce, and fought Nchuz which disturbs her life and leads to divorce, preventive steps and stages of reform distancing the sex from The power of masculinity and the language of conflict, and remove women from humiliation and humiliation, and maintain the relationship between parents Children. The centrality of the Quran and the moderation of Islam in dealing with divorce are based on its miraculousness, which does not leave a minor or a large one except that it is counted. He did not prohibit divorce so as not to be extreme, and he did not give him absolute permission so as not to be unjust. He was between the custodian of the conditional marriage And he maintained the sanctity of the human relationship in the event of separation between the spouses. He was merciful to the man and he is marrying him, and he is also merciful to him, and he is authorized to divorce him, and he is merciful and he hates this divorce.